2013
DOI: 10.1002/chem.201204001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Methyltrioxorhenium‐Catalyzed Deoxydehydration of Polyols: A New Pathway Revealed

Abstract: Polyols pathway probed: Density functional theory computations reveal that the methyltrioxorhenium-catalyzed deoxydehydration of polyols follows pathway C, which is energetically more favorable than the previously proposed pathways A and B. In addition to serving as solvent/reductant, the alcohol also acts as a shuttle to greatly facilitate various hydrogen-transfer steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
71
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 46 publications
(46 reference statements)
9
71
1
Order By: Relevance
“…In agreement with the computational investigation of the mechanism by Wang and co-workers, [14] we suggest that the active catalyst is XReO 3 ·L and that it can undergo reduction to XReO 2 ·L, which thus favors the right-hand side of the pathway shown in Scheme 2. To account for the fact that the rate increases if the diol concentration decreases, we suggest additionally that XReO 3 ·L can also undergo deactivation to a rhenium(VII) diolate XReO 2 (diolate) according to the following equilibrium [Eq.…”
Section: Acceleration Of the Reactionsupporting
confidence: 81%
See 4 more Smart Citations
“…In agreement with the computational investigation of the mechanism by Wang and co-workers, [14] we suggest that the active catalyst is XReO 3 ·L and that it can undergo reduction to XReO 2 ·L, which thus favors the right-hand side of the pathway shown in Scheme 2. To account for the fact that the rate increases if the diol concentration decreases, we suggest additionally that XReO 3 ·L can also undergo deactivation to a rhenium(VII) diolate XReO 2 (diolate) according to the following equilibrium [Eq.…”
Section: Acceleration Of the Reactionsupporting
confidence: 81%
“…In addition, the law of mass action is only obeyed in dilute solutions (not the case here), and the value of K is dependent on the polarity of the solution; therefore, a variation of the concentration of, for example, 3-octanol will not only shift the equilibrium but also change the value of K. The addition of the nonreactive nucleophile 1-decanol shifts the equilibrium shown in Equation (4) towards the active catalyst, which explains the higher observed rate in entry 10 compared to that in entry 4 in Table 1. The same is not true if 3-octanone is added, which is because of the less nucleophilic nature of ketones and, more important, the inability of ketones to stabilize the transition state for the reduction of XReO 3 ·L to XReO 2 ·L: As shown by Wang and co-workers, [14] two alcohol molecules are coordinated to the Re complex in the transition state-one is oxidized and the other, which could also be a nonreactive primary alcohol, stabilizes the transition state. Furthermore, Wang and co-workers also found that an alcohol molecule served as a H-transfer shuttle in the condensation between CH 3 ReO 3 and the diol-at low alcohol concentrations, the equilibrium in Equation (4) might, therefore, be reached more slowly.…”
Section: Acceleration Of the Reactionmentioning
confidence: 77%
See 3 more Smart Citations